An early prediction of postprandial glycemia evolution using the MD001 algorithm: a muticentre prospective trial: EGHYA: a multicentre prospective trial - Di Costanzo, Veronique; Scheapelynck, Pauline; Gardan, Vincent; Lafond, Sophie; Gouze, Jean Noel (Cellular and Molecular Biology, 2025)
To date, the closed-loop system represents the best commercialized management of type 1 diabetes. However, mealtimes still require carbohydrate estimation and are often associated with postprandial hyperglycemia which may contribute to poor metabolic control and long -term complications. A multicentre, prospective, non-interventional clinical trial was designed to determine the effectiveness of a novel algorithm to predict changes in blood glucose levels two hours after a usual meal. Forty patients were included, and 765 meals were analyzed of which 278 were followed by a postprandial hyperglycemic event i.e. value > 160 mg/dL two hours after the start of the meal. The developed algorithm correctly predicts the postprandial hyperglycemia risk or absence of risk in 87% of cases. The results suggest that early prediction of the glycemic evolution within a few minutes after the end of a meal can considerably improve the postprandial hyperglycemia management and thus reduce the associated emotional burden. The study was supported by M-DT1 SAS, France.